2001
DOI: 10.1074/jbc.m011177200
|View full text |Cite
|
Sign up to set email alerts
|

Damaged DNA-binding Protein DDB Stimulates the Excision of Cyclobutane Pyrimidine Dimers in Vitro in Concert with XPA and Replication Protein A

Abstract: Human cells contain a protein that binds to UV-irradiated DNA with high affinity. This protein, damaged DNA-binding protein (DDB), is a heterodimer of two polypeptides, p127 and p48. Recent in vivo studies suggested that DDB is involved in global genome repair of cyclobutane pyrimidine dimers (CPDs), but the mechanism remains unclear. Here, we show that in vitro DDB directly stimulates the excision of CPDs but not (6 -4)photoproducts. The excision activity of cell-free extracts from Chinese hamster AA8 cell li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
82
0
2

Year Published

2002
2002
2014
2014

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 85 publications
(85 citation statements)
references
References 49 publications
1
82
0
2
Order By: Relevance
“…In support of this hypothesis, introduction of excess recombinant UV-DDB to in vitro reconstituted NER reactions resulted in inhibition of repair of (6-4) photoproducts (8,9). In addition, in vivo studies of fluorescently tagged UV-DDB binding have reported immobile binding of UV-DDB to DNA for up to 4 h in XP-A cells (41).…”
Section: Damage Recognition Is a Multistep Kinetic Cascade Culminatinmentioning
confidence: 68%
See 1 more Smart Citation
“…In support of this hypothesis, introduction of excess recombinant UV-DDB to in vitro reconstituted NER reactions resulted in inhibition of repair of (6-4) photoproducts (8,9). In addition, in vivo studies of fluorescently tagged UV-DDB binding have reported immobile binding of UV-DDB to DNA for up to 4 h in XP-A cells (41).…”
Section: Damage Recognition Is a Multistep Kinetic Cascade Culminatinmentioning
confidence: 68%
“…During global genomic repair, cyclobutane pyrimidine dimers (CPDs) and pyrimidine(6-4)pyrimidone photoproducts [(6-4) photoproducts] are repaired by the nucleotide excision repair (NER) pathway that recognizes and excises bulky helix distorting lesions in the genome (6, 7). The recognition of CPD lesions in UV-damaged chromatin is mediated by UV-damaged DNAbinding protein (UV-DDB), composed of the tightly associated heterodimer of damage-specific DNA binding protein (DDB) 1 (p127) and DDB2 (p48) (5,8). Following surveillance and CPD identification by UV-DDB, NER proceeds via lesion handover to XPC-hHR23B-centrin2 (XPC) followed by damage verification, helix opening and stabilizing of the repair intermediates, dual incision of the DNA in the context of the lesion, repair synthesis, and DNA ligation (7).…”
mentioning
confidence: 99%
“…However, the degree of relocation and association of XPA with the damaged sites observed in wild type cells was minimal, and therefore the results obtained monitoring XPA relocalization with the XPC cells are difficult to interpret (21). In addition to XPC-hHR23B and the XPA-RPA complex, the damaged DNAbinding protein DDB (heterodimer p127 and p48) also preferentially binds damaged DNA and is specifically involved in the repair of DNA adducts that fail to cause a large change in thermal stability of the duplex DNA (17,41). Whether these protein factors play a role prior to RPA-XPA binding or whether there is a higher order recognition complex remains to be determined.…”
Section: Discussionmentioning
confidence: 98%
“…There is also evidence that the XPChHR23B protein complex may initiate recognition of DNA damage for the global genomic repair pathway of NER (15). Recent evidence also implicates the DDB heterodimer in damage recognition because the complex binds damaged DNA with high affinity (16) and can dramatically increase the repair rate of certain DNA adducts, including cyclobutane pyrimidine dimers in conjunction with XPA and RPA (17). In addition, the p48 subunit of DDB has been demonstrated to localize to the sites of UV-induced DNA damage independent of XPA and XPC (18).…”
Section: Nucleotide Excision Repair (Ner)mentioning
confidence: 99%
“…DDB strongly binds to DNA damages caused by UV light, including (6-4) photoproducts and trans,syn-cyclobutane pyrimidine dimers, yet it does not have a strong affinity for cis,syn-cyclobutane pyrimidine dimers, the most abundant UV photoproduct (5,(7)(8)(9)(10)(11).…”
mentioning
confidence: 99%